Membrane Filtration of Nanoscale Biomaterials: Model System and Membrane Performance Evaluation for AAV2 Viral Vector Clarification and Recovery - Mara Leach; Kearstin Edmonds; Emily Ingram; Rebecca Dutch; Ranil Wickramasinghe; Malgorzata Chwatko; Dibakar Bhattacharyya (Nanomaterials)
The growing demand for viral vectors as nanoscale therapeutic agents in gene therapy necessitates efficient and scalable purification methods. This study examined the role of nanoscale biomaterials in optimizing viral vector clarification through a model system mimicking real AAV2 crude harvest material. Using lysed HEK293 cells and silica nanoparticles (20 nm) as surrogates for AAV2 crude harvest, we evaluated primary (depth filters) and secondary (membrane-based) filtration processes under different process parameters and solution conditions. These filtration systems were then assessed for their ability to recover nanoscale viral vectors while reducing DNA (without the need for endonuclease treatment), protein, and turbidity. Primary clarification demonstrated that high flux rates (600 LMH) reduced the depth filter’s ability to leverage adsorptive and electrostatic interactions, resulting in a lower DNA removal. Conversely, lower flux rates (150 LMH) enabled >90% DNA reduction by maintaining these interactions. Solution conductivity significantly influenced performance, with high conductivity screening electrostatic interactions, and the model system closely matching real system outcomes under these conditions. Secondary clarification highlighted material-dependent trade-offs. The PES membranes achieved exceptional AAV2 recovery rates exceeding 90%, while RC membranes excelled in DNA reduction (>80%) due to their respective surface charge and hydrophilic properties. The integration of the primary clarification step dramatically improved PES membrane performance, increasing the final flux from ~60 LMH to ~600 LMH. Fouling analysis revealed that real AAV2 systems experienced more severe and complex fouling compared to the model system, transitioning from intermediate blocking to irreversible cake layer formation, which was exacerbated by nanoscale impurities (~10–600 nm). This work bridges nanomaterial science and biomanufacturing, advancing scalable viral vector purification for gene therapy.